Same-day discharge after minimal invasive hysterectomy: Applications for improved value of care. (April 2021) - Qi, Meiyuzhen; Lopa, Samia; Adambekov, Shalkar; Harris, John A.; Mansuria, Suketu; Edwards, Robert P.; Linkov, Faina
Highlights: The uptake of same-day discharge (SDD) for minimally invasive hysterectomies (MIH) was found to be increasing in a large healthcare system over years since the implementation of SDD initiative. The uptake of SDD for MIH was associated with lower surgical complication rate. The successful uptake of SDD across different specialty types in heterogeneous hospitals of UPMC proved the feasibility of applying SDD initiative across the country. Compared with other specialties, the uptake of SDD was most prominent among urogynecologists. Abstract: Objective: Hysterectomy is one of the most common surgical procedures. Same-day discharge (SDD) is increasingly utilized for minimally invasive hysterectomies, but its uptake varies across healthcare systems and surgical specialties. An evidence-based initiative was developed to aid in the incorporation of SDD into the practice of minimally invasive hysterectomy (MIH) in the UPMC Health System. The objective of this study was to identify trends of SDD utilization across various gynecologic specialties at UPMC, as well as evaluate the impact of SDD on length of stay (LOS) and complications after the implementation of SDD initiative. Study design: We retrospectively identified 5554 patients who underwent MIH between 2014 and 2017 and were eligible for SDD, as determined by physicians and authorized by patients' insurance plans. Multivariable logistic regression models evaluated the trend of SDD utilization among four specialty types (general gynecologists, urogynecologists, specialized minimally invasive surgeons, and oncologists) and trends in complications. Multivariable logistic and linear regression models were applied to compare complications and LOS between patients with SDD vs. those with overnight admissions. Results: SDD utilization increased from 28.55% to 74.99% during the study period. SDD significantly increased over the study period for all specialty types, with urogynecologists having the highest uptake from 3.9% in 2014 to 95.8% in 2017 (p<.01). After adjusting for year, specialty types, MIH procedure type, and total case time, SDD utilization was associated with shorter mean LOS (p<.01); such that mean LOS was 764.43 min (95% CI: 735.46–793.40) for SDD patients and 2041.84 min (95% CI: 2015.99–2067.70) for patients with overnight admissions. SDD was also associated with 42% lower odds (95% CI: 0.37−0.93, p=.02) of complications compared with patients with overnight admissions. Conclusion: Same-day discharge uptake increased over years and was associated with lower odds of complications and decreased length of stay. More studies are needed to explore same-day discharge process to improve patient outcomes, patient satisfaction, and value of care.